2017
DOI: 10.3389/fendo.2017.00154
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic and Metabolic Effects of Two Long Bouts of Moderate-Intensity Exercise in Men with Normal Glucose Tolerance or Type 2 Diabetes

Abstract: BackgroundThe glycemic and insulinemic responses following 30–60 min of exercise have been extensively studied, and a dose–response has been proposed between exercise duration, or volume, and improvements in glucose tolerance or insulin sensitivity. However, few studies have examined the effects of longer bouts of exercise in type 2 diabetes (T2D). Longer bouts may have a greater potential to affect glucagon, interleukin-6 (IL-6) and incretin hormones [i.e., glucagon-like peptide-1 (GLP-1) and glucose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…Accordingly, our results likely underestimate the true magnitude of enrichment of genes in SST neurons and still cannot completely circumvent the possibility that some genes identified in this study are markers of neurons as a whole and not specifically SST neurons. An additional experimental caveat is that use of different strains for comparison may have influenced the differential gene expression results, since Sst-ires - Cre has been shown to affect the expression of some genes 84 . In future studies, more specific comparisons could be made if, instead of using total spinal nuclei for comparison, other Cre lines are used that mark specific neuronal populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our results likely underestimate the true magnitude of enrichment of genes in SST neurons and still cannot completely circumvent the possibility that some genes identified in this study are markers of neurons as a whole and not specifically SST neurons. An additional experimental caveat is that use of different strains for comparison may have influenced the differential gene expression results, since Sst-ires - Cre has been shown to affect the expression of some genes 84 . In future studies, more specific comparisons could be made if, instead of using total spinal nuclei for comparison, other Cre lines are used that mark specific neuronal populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the acute aerobic exercise session performed in the postprandial state on glucose levels observed here is the classical well-known effect of glucose reduction, which is related to increased plasma membrane content of GLUT4 (31). Overall, lower glucose levels were described at the end of the exercise performed in the fasting state or after lunch (13), and a single bout of exercise reduced the prevalence of hyperglycemia over the subsequent 24-h period (26). A systematic review showed that the association between the timing of exercise and the timing of meals plays an important role in improving glucose control in individuals with type 2 diabetes, with more important benefits whether the exercise was conducted between 30 and 60 min after the meal consumption as compared to a no exercise control condition (32).…”
Section: Discussionmentioning
confidence: 52%
“…The incretin GLP-1 plays a crucial role in maintaining metabolic homeostasis, since it induces postprandial insulin release and suppresses glucagon secretion; although there are no systematic differences in the nutrient-induced secretion of GLP-1 between healthy and type 2 diabetic subjects, there are characteristic abnormalities in the insulinotropic and glucagonostatic activities among them (12). The hormonal response to exercise could be affected in diabetes: postprandial suppression of glucagon, increase of GLP-1, and no change in insulin levels was observed in diabetes patients one day after performing two long bouts of exercise (13). Although other studies have shown no change in insulin levels after acute sessions of aerobic exercise (14,15), other authors reported a reduction in these levels (16), while glucagon levels were found to have increased after aerobic exercise (17), and GLP-1 levels decreased during post-dinner resistance exercise (18).…”
Section: Introductionmentioning
confidence: 99%
“…Structured lifestyle interventions that include at least 150 min/week of physical activity and dietary changes resulting in weight loss of 5-7% are recommended to prevent or delay the onset of type 2 diabetes in populations at high risk and with prediabetes [10]. To date, the influence of physical activity on the pathogenetic risk factors of overweight and obesity has been proven, including optimization of the secretion of adipose tissue hormones, incretins and reduction of low-gradient nonspecific inflammation [11,12].…”
Section: Imbalance Of Adipokines Cytokines and Incretins As A Pathoge...mentioning
confidence: 99%